Influence of caffeine in lipolysis and glucose metabolisn during class indoor cycling - Helou, Tatiana Tatiana Helou (2013)
Caffeine stimulates fatty acid mobilization by increased catecholamine release. The fatty acid oxidation spares muscle carbohydrate stores resulting delaying fatigue. Objective: The aim of this study was to investigate whether the influence of caffeine on lipolysis induces a reduction in blood glucose levels during an indoor cycling class. Materials and methods: Primary, clinical, prospective, analytical, controlled, comparative, observational study, performed at a single center. Participated in the study 19 men with mean age of 35 ± 8.1 years, physically active for at least 6 months 3 times a week. The subjects were randomly assigned to placebo (n = 7) and caffeine group (n = 12). The caffeine group received 5 mg/kg of caffeine 30 min before carrying out a ciclism indoor class. All participants ingested the same pre-test meal and fasted for 8 hours before the test. Two blood samples were collected, one at arrival, prior to the ingestion of caffeine and the second immediately after the exercise. Total cholesterol, triglycerides, HDL, LDL, VLDL, glucose, urea, creatinine, uric acid and lactate were measured. The study was double blind and statistical analysis was used from the Student's ttest, considering significant pvalues <0.05. Results: There was statistical difference only in HDL (p<0.05) among both CG and PG and between individuals of each group. We conclude that caffeine consumption under the conditions of this study did not alter the lipid profile in order to induce a reduction in blood glucose levels and delay fatigue during an indoor cycling class.